Electrical Safety Handbook - Neitzel, Dennis K; Winfield, Al; Capelli-Schellpfeffer, Mary (McGraw-Hill Education, 2019)
On-the-job electrical safety essentials-thoroughly revised for the latest procedures and standardsThis fully updated electrical safety guide is a practical, illustrated source of life-saving information designed for specific work environments. The book has been fully revised and expanded to conform to every current major electrical standard, including NEC, NESC, NFPA70E, IEEE 1584, and OSHA. Written by experts in electrical operations, maintenance, engineering, construction, and safety, Electrical Safety Handbook, Fifth Edition provides the most up-to-date safety strategies in an easy-to-use format. The book delivers complete details on electrical hazards, safety equipment, management, training, regulatory and legal requirements, accident prevention, and much more. You will find new sections on electrical grounding, heat transfer theory as it relates to the human body, and the medical aspects of electrical trauma. *Contains comprehensive coverage of every subject on the exam*Includes updated electrical grounding concepts and applications*Written by a team of electrical safety experts